The assessment of Ukraine’s prospects for the fossil fuels phase-out - Radomska, Margaryta Myroslavivna; Ponomarenko, Marina Serhiyivna; Nazarkov, Taras Ihorovych (Science-based technologies, 2020)
The running out of fossil fuels reserves and growing degradation of the environment quality have contributed to the formation of new vision of economy development, based on transition to green energy. An essential part of this process is the abandonment of fossil fuels extraction and processing facilities, as well as complete ban on their further use. As of today Ukraine has a range of serious problems in the field of energy supply provision, due to lack of domestic energy minerals reserves and dependence on their import. Moreover, the complicated geopolitical situation in the region makes the state government seek for alternative sources for the diversification of supply. As a result, Ukraine has even more reasons for phasing-out fossil fuels, than other countries of the world. The study of the existing international agreements and national strategies adopted in European region showed that most developed countries have already started to implement some elements of the Paris agreement on the abandonment of fossil fuels. In most cases this refers to limitation on cars with internal combustion engines at cities and decommissioning of coal powered thermal plants. The pros and cons of implementing state plans on changing carbon based energy to alternative power generation strategies was assessed using the method of PESTLE analysis, which defines the influence of external factors and risks for any strategy, in particular political, economic, social, technological, legal and environmental. The central problem in the process of moving away from fossil fuels based economy is finding efficient substitution for them among alternative renewable sources of energy with minimal impacts on the environment. To analyze the benefits of any possible alternative the matrix method was used, in which all alternatives are graded by the scale in relation to a set of valuable factors/parameters. The results of the PESTLE analysis show that social and environmental factors have the highest contributing potential to the process, while political and economic factors may form both positive and negative drivers, limiting the efficiency of other factors. The comparison of the substitution alternatives, including use of geothermal energy, bioenergy, increase in nuclear, wind or solar energy and energy mix, demonstrated that the energy mix is the one with the best outcomes at lower investments. However, it needs careful planning and localization of solutions. Another important finding is that the fossil fuels abandoning for Ukraine is impossible without the nuclear energy input. Thus, it is concluded that there is a need to work thoroughly on the improvement of energy efficiency, as it can reduce the volume of the necessary energy supply.